Vertical differentiation drives the changes in the main microflora and metabolites of carbon and nitrogen cycling in the early freeze–thaw period in the Qinghai Lake Basin - Zhang, Ni; Chen, Kelong; Wu, Chenxi; Jiang, Hongchen; Du, Yangong; Chen, Zhirong; Wang, Xinye; Qi, Desheng; Yang, Ziwei (Frontiers in Microbiology, 2024)
Global climate change has altered the frequency of soil freeze-thaw cycles, but the response of soil microorganisms to different elevation gradients during the early freeze-thaw period remains unclear. So far, the influence of the altitudinal gradient on the microbial community and metabolic characteristics in the early freeze-thaw period of the Qinghai Lake Basin remains unclear. To this end, we collected soil at different elevations in the early freeze-thaw period of the Qinghai Lake Basin and investigated the influence of the elevation gradient on soil microbial community characteristics and soil metabolic processes as well as the corresponding environmental driving mechanism by high-throughput sequencing and LC-MS (Liquid Chromatograph-Mass Spectrometer) nontargeted metabolite determination. The results showed that Proteobacteria were the dominant microflora in the Qinghai Lake Basin. The dominant phyla associated with carbon and nitrogen are Proteobacteria and Firmicutes, both of which are significantly affected by elevation. The soil physicochemical factors jointly affected the soil microbial communities and metabolism. Total phosphorus nitrate nitrogen and pH were the main driving factors of the microbial community, and metabolites were sensitive to changes in chemical factors. In short, the microbial community structure and function, soil physicochemical factors and soil metabolic processes were significantly affected by the altitudinal gradient in the early freeze-thaw period, while the microbial community diversity showed no significant response to the altitudinal gradient. The results of this study provide a solid basis for future research on changes in alpine ecosystem under the influence of climate change and at the same time have significant implications for elucidating the mechanisms of the carbon and nitrogen cycle.